One Health & food systems research from CGIAR - Hung Nguyen-Viet (Elsevier, 2025)
Background: CGIAR is a global research partnership dedicated to transforming food, land, and water systems in a climate crisis. CGIAR is implementing a portfolio of 32 research initiatives (2022–24) including CGIAR One Health initiative to address zoonotic and foodborne diseases and antimicrobial resistance in food systems in LMIC settings. In addition, the International Livestock Research Institute (ILRI), as a member of CGIAR implements a One Health program that aims to manage effectively or eliminate livestock, zoonotic and foodborne diseases that matter to poor people through generation and utilization of new knowledge, technologies and products.